Smart Medication Adherence System using IoT for Elderly Patients - Mat Nasir, Fahmi Sharmila; Omar Abu Hassan; Muhammad Rusydi Muhammad Razif (Progress in Engineering Application and Technology, 2022)
The availability of electronic monitoring has developed a huge possibility in increasing elders’ adherence towards medication. With the help of IoT platform, the system can be connected to the medical practitioner, care giver, and even the patients’ mobile devices. The medication adherence monitoring system consists of electronic components such as sensors that can validate patients’ medication intake and sent the data collected to those in charge of taking care of the patients. The Smart Medication Adherence system using IoT for elderly patient is seeking an improvement towards the classic way of taking medicine among elderly patient who lives away from their caregiver. With the help from IoT (Internet of Things), caregiver can monitor their patients’ medication intake without having to be with them all the time. This project presents an IoT-based medication monitoring and reminder system that allow communication with the caregiver through phone call using a platform called IFTTT. In order to validate patient’s consumption, magnetic switch sensor that were attached to the pillbox will detect whether patient open or close the pill-box cap. In addition, the Force Sensitive Resistor (FSR) sensor were used to detect the differences in force or pressure of the pills during consumption. The system is programmable that enables the caregiver or patients to determine the schedule of their prescription. Using NodeMcu, this device will be connected to Wi-Fi and enable the transmission of information to the IoT platform.